Protease-Activated Receptors – Key Regulators of Inflammatory Bowel Diseases Progression - Jacenik D; Fichna J; Małecka-Wojciesko E; Mokrowiecka A (Dove Medical Press, 2021)
Damian Jacenik,1 Jakub Fichna,2 Ewa Małecka-Wojciesko,3 Anna Mokrowiecka3 1Department of Cytobiochemistry, Faculty of Biology and Environmental Protection, University of Lodz, Lodz, Poland; 2Department of Biochemistry, Faculty of Medicine, Medical University of Lodz, Lodz, Poland; 3Department of Digestive Tract Diseases, Faculty of Medicine, Medical University of Lodz, Lodz, PolandCorrespondence: Damian JacenikDepartment of Cytobiochemistry, Faculty of Biology and Environmental Protection, University of Lodz, 141/143 Pomorska St., 90-236 Lodz, PolandTel +48 42 635 52 99Fax +48 42 635 44 84Email damian.jacenik@biol.uni.lodz.plAbstract: The pathogenesis and course of inflammatory bowel diseases are related to both immune system disorders and dysfunction of colon permeability. Moreover, co-existing diseases in patients with Crohn's disease and ulcerative colitis are identified. Currently, there are some therapeutic strategies that affect the function of cytokine/s causing inflammation in the intestinal wall. However, additional approaches which target other components of inflammatory bowel diseases pathogenesis are still needed. Accumulating evidence suggests that proteases and protease-activated receptors seem to be responsible for colitis progression. Experimental and observational studies showed alteration of protease-activated receptors expression in the colon of patients with Crohn's disease and ulcerative colitis. Furthermore, it was suggested that the expression of protease-activated receptors correlated with inflammatory bowel diseases activity. Moreover, regulation of protease-activated receptors seems to be responsible for the modulation of colitis and clinical manifestation of inflammatory bowel diseases. In this review, we present the current state of knowledge about the contribution of protease-activated receptors to Crohn's disease and ulcerative colitis and its implications for diagnosis and treatment.Keywords: inflammatory bowel disease, Crohn's disease, ulcerative colitis, colitis, immune response, proteinase-activated receptor